2020
DOI: 10.21272/bel.4(2).56-74.2020
|View full text |Cite
|
Sign up to set email alerts
|

Business Open Big Data Analytics to Support Innovative Leadership and Management Decision in Canada

Abstract: This paper summarizes how social media and other technologies continue to proliferate; the shifting economic landscape will precipitate more adaptive approaches for managers attempting to understand the multi-dimensional virtual aspects of communication with the artificial intelligence aspect. Also, we discover the different existing support of big data analytics to make a rational business decision. The methodology is the systematization literature sources within this context and approaches for the underlinin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
23
0
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
8
2

Relationship

3
7

Authors

Journals

citations
Cited by 45 publications
(27 citation statements)
references
References 88 publications
0
23
0
1
Order By: Relevance
“…The criteria for administrators included identified as any ethnicity and being employed at a Massachusetts community college as a director, coordinator, dean, or vice president. Both faculty and administrators were over 18 years old (Delanoy & Kasztelnik, 2020). Krueger and Casey (2015) suggested having 5 to 8 participants.…”
Section: Methodsmentioning
confidence: 99%
“…The criteria for administrators included identified as any ethnicity and being employed at a Massachusetts community college as a director, coordinator, dean, or vice president. Both faculty and administrators were over 18 years old (Delanoy & Kasztelnik, 2020). Krueger and Casey (2015) suggested having 5 to 8 participants.…”
Section: Methodsmentioning
confidence: 99%
“…The result abets in the engagement of various attributes of the online adjunct faculties working environment, which consists of instruction, employee development, and communication with academic leadership. Authors believe that the prior study (Delanoy & Kasztelnik, 2020) showed that the business open big data analytics can support innovative educational process by using the novel technology. Authentic leadership develops from ethical values and stem from leaders genuinely encompassing actions of trustworthy, reliable, and genuine individuals.…”
Section: Authenticmentioning
confidence: 99%
“…After a person has mastered the social awareness necessary to recognize emotions in others, they can use that along with the previous two, they work together to motivate and inspire others. Goleman (1998) indicated that unlike IQ which is stable and relatively unchangeable, emotional intelligence can be improved through learning and practice (Delanoy and Kasztelnik, 2020).…”
Section: Emotional Intelligencementioning
confidence: 99%